Sociodemographic and Academic Characteristics of the Admission Profile of Students, Faculty of Dentistry, University of Costa Rica 2007-2014 - Gutiérrez-Marín, Natalia (2022)
The objective of this research was to determine some of the sociodemographic and academic characteristics of the students who entered the Dentistry career in the period 2007 to 2014. Data was collected from 673 student files. The variables considered were sex, admission age, marital status, children, nationality, place of origin, high school of origin, and admission exam score. The data was obtained from the database of the Student Applications System, the physical files, and the Supreme Electoral Tribunal of Costa Rica. Descriptive statistics were performed, establishing the absolute and relative frequency of the variables. The Mann-Whitney test was used to determine if there were statistically significant differences between the admission exam and the established sociodemographic variables (p<0,05, IC 95%). 68,4% of the students are female. The average age was 18.4 years (SD=2,41). 99,0% of the students are from Costa Rica. 99,3% were single and only 0,9% had children. The largest number of students entered through an admission exam (78.9%) and 50.7% studied at a public high school. Regarding the address, 77.9% of the subjects resided in the Greater Metropolitan Area. The average grade of the admission exam was 613,8 (SD=49,95). There was a statistically significant difference between the entrance exam grade and the different types of high schools of origin. The group of students who entered to train as Dentists at the University of Costa Rica from 2007 to 2014 was a population with an average age of entry of 18,4 years, Costa Rican, predominantly female, single, without children, from geographic areas within the Greater Metropolitan Area (GMA), graduated from public schools with an average admission exam grade of 612,2.